PMP Exam Prep : Accelerated Learning to Pass the Project Management Professional (PMP) Exam - Mulcahy, Rita (Minnetonka, Minnesota RMC Publications, 2018)
Offering hundreds of sample questions, thought-provoking exercise, and critical time-saving tips, this book will help you pass the PMP exam on your first try. Will teach you tricks of the trade for passing the exam and help you identify gaps in your knowledge
Include Index
Keywords: Project management -- Project management--Examinations